Cluster Analysis Using the Hierarki Method For Grouping Sub-Districts in The District Steps Based on Health Indicators - Khairun Nisa; Rina Filia Sari; Hendra Cipta; Ismail Husein (UIN Sumatera Utara, 2020)
Cluster analysis is a method used to group objects based on similarity of characteristics they have. Cluster analysis using the hierarchy method is a method with a grouping process that is used in stages. Health is a condition where a person is not sick, has no complaints, and can carry out daily activities. To find out information about the level of health in Langkat Regency, it is necessary to use the grouping method. The grouping was carried out in 23 districts in Langkat Regency. The purpose of this study is to classify sub-districts in Langkat Regency which have similar characteristics based on health indicators through the square euclidian distance is used to measure the similarity between object pairs and the ward method. From the results of cluster analysis using the ward method.